2005
DOI: 10.1007/s10994-005-5824-7
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Feature Extraction for Classifying Audio Data

Abstract: Abstract. Today, many private households as well as broadcasting or film companies own large collections of digital music plays. These are time series that differ from, e.g., weather reports or stocks market data. The task is normally that of classification, not prediction of the next value or recognizing a shape or motif. New methods for extracting features that allow to classify audio data have been developed. However, the development of appropriate feature extraction methods is a tedious effort, particularl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 127 publications
(58 citation statements)
references
References 19 publications
0
55
0
3
Order By: Relevance
“…We believe that these features, extracted over these window lengths, are diverse enough to capture important historical information from the signals to be used in models. There are other features that could be extracted, or features can be extracted using automated and supervised methods (Guo, Jack, & Nandi, 2005;Mierswa & Morik, 2005;Hamel & Eck, 2010). …”
Section: Temporal Feature Extractionmentioning
confidence: 99%
“…We believe that these features, extracted over these window lengths, are diverse enough to capture important historical information from the signals to be used in models. There are other features that could be extracted, or features can be extracted using automated and supervised methods (Guo, Jack, & Nandi, 2005;Mierswa & Morik, 2005;Hamel & Eck, 2010). …”
Section: Temporal Feature Extractionmentioning
confidence: 99%
“…The reason was that the method shall only use basic methods thus Fast Fourier Transformation has been used. Elementary feature extraction operations can be executed in any order and allow the creation of a set of feature extraction operations the can be different for each problem [21]. This makes elementary extraction operations also good for machine learning.…”
Section: Feature Extraction and Sensor Fusionmentioning
confidence: 99%
“…It was shown that some of the constructed features could indeed improve music classification performance relative to conventional features. Another such example was presented by Mierswa and Morik [25], where method trees consisting of ad hoc features for a given audio signal were introduced. The trees were automatically generated with GP by combining elementary feature extraction methods.…”
Section: Related Workmentioning
confidence: 99%